2020
DOI: 10.1021/acs.bioconjchem.0c00126
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Nanomaterials with Inherent Optical and Magnetic Properties for Bioimaging and Imaging-Guided Nucleic Acid Therapy

Abstract: Nucleic acid therapy is and will continue to be of great interest in cancer treatment. The development of nanocarriers with high nucleic acid loading capacity, low toxicity, and specific targeting, with excellent pharmacokinetic/pharmacodynamic profiles, will enable us to realize safe and effective nucleic acid therapy. Tremendous efforts have been directed toward the production of optimized theranostic nanocarriers that can simultaneously provide treatment and real-time monitoring to aid researchers and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…We therefore set out to identify fluorescence labeled analogs to perform FRET based proximity studies and track the localization of the dendrimers during transfection. Indeed, various labeling studies reported on siRNA or transfection reagents , have been shown to provide useful insight into the transfection process. Considering that a variety of dendrimer core modifications were compatible with siRNA transfection if the dendrimer branches were kept constant, we designed our fluorescently labeled dendrimers by modifying the dendrimer core with hydrophobic fluorescent labels.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore set out to identify fluorescence labeled analogs to perform FRET based proximity studies and track the localization of the dendrimers during transfection. Indeed, various labeling studies reported on siRNA or transfection reagents , have been shown to provide useful insight into the transfection process. Considering that a variety of dendrimer core modifications were compatible with siRNA transfection if the dendrimer branches were kept constant, we designed our fluorescently labeled dendrimers by modifying the dendrimer core with hydrophobic fluorescent labels.…”
Section: Introductionmentioning
confidence: 99%
“…[158] With the merging of dual-function performance, nanomaterials with intrinsic optical and magnetic characteristics were employed for both fluorescence bioimaging and imaging-guided nucleic acid therapy. [159] Additionally, nanomaterials were adopted for reducing the background signals and increasing the cellular uptake efficiency. For example, Wang et al designed an aptamer-carboxyfluorescein/graphene oxide nanocomplex, achieving the molecular probing in living cells.…”
Section: Integrated Nucleic Acids For Imagingmentioning
confidence: 99%
“…The incorporation of siRNA into polymer-or lipid-coated iron oxide NPs generates multifunctional theranostic platforms that are suitable for simultaneous imaging and gene therapy (Figure 8E). 145,146 Since iron oxide NPs are capable of remotely controlled targeting and heating via the application of an external magnetic field, targeted transfection and combination therapy can be achieved. 147 Metal-organic frameworks (MOFs), formed by sensitive coordination bonds between inorganic metal ions and organic ligands, are another interesting vector due to the high surface area, porosity, and biodegradability (Figure 8F).…”
Section: Llmentioning
confidence: 99%